Petites scènes de la vie quotidienne à travers le Vocabulario de refranes de Correas (1627) - Françoise Cazal (Les Cahiers de Framespa)
The 25.000 proverbs and proverbial expressions in the Vocabulario de refranes de Gonzalo Correas provide unending source material for thematic studies on Spanish Golden Age society. To the proverbs studied here because of their references to daily life shall be added other familiar scenes that were included by the compiler in his commentaries. These proverbs and anecdotes that concern many aspects of society are studied here as «literalized» reflections of the way of life and ways of thinking in Spanish society as the products that lay somewhere at the borderline of social acts and literary acts. At the end of the article a translation into French will enable the reader a better understanding of the literal sense of these proverbs that enclose a sometimes obscure meaning.